Optimization, selection and feasibility study of solar parabolic trough power plants for Algerian conditions. (1st September 2015) - Boukelia, T.E.; Mecibah, M.S.; Kumar, B.N.; Reddy, K.S.
Highlights: Evaluation of solar resources in the absence of measured data. Optimization of 2 PTSTPPs integrated with TES and FBS and using oil and salt as HTFs. 4E comparative study of the two optimized plants alongside the Andasol 1 plant. The salt plant resulting as the best one and has been chosen for the viability study. Tamanrasset is the best location for construction of PTSTPPs. Abstract: In the present study, optimization of two parabolic trough solar thermal power plants integrated with thermal energy storage (TES), and fuel backup system (FBS) has been performed. The first plant uses Therminol VP-1 as heat transfer fluid in the solar field and the second plant uses molten salt. The optimization is carried out with solar multiple (SM) and full load hours of TES as the parameters, with an objective of minimizing the levelized cost of electricity (LCOE) and maximizing the annual energy yield. A 4E (energy–exergy–environment–economic) comparison of the optimized plants alongside the Andasol 1 as reference plant is studied. The molten salt plant resulting as the best technology, from the optimization and 4E comparative study has been chosen for the viability analysis of ten locations in Algeria with semi-arid and arid climatic conditions. The results indicate that Andasol 1 reference plant has the highest mean annual energy efficiency (17.25%) and exergy efficiency (23.30%). Whereas, the highest capacity factor (54.60%) and power generation (236.90 GW h) are exhibited by the molten salt plant. The molten salt plant has least annual water usage of about 800, 482 m 3, but demands more land for the operation. Nevertheless the oil plant emits the lowest amount of CO2 gas (less than 40.3 kilo tonnes). From the economic viewpoint, molten salt seems to be the best technology compared to other plants due to its lowest investment cost (less than 360 million dollars) and lower levelized cost of electricity (LCOE) (8.48 ¢/kW h). The viability study proposes Tamanrasset, as the best location for erection of a parabolic trough solar thermal power plant with a low LCOE of 7.55 ¢/kW h, and a high annual power generation (more than 266 GW h). According to the feasibility analysis, the semi-arid and arid Algerian sites are suitable for realization of PTSTPP with integrated TES and FBS; especially the southern locations (19°N–32°N, 8°W–12°E).